Analisis Risiko Kegagalan Motor Long Travel Merk ABUS dengan Metode Failure Mode and Effect Analysis (FMEA) dan Fishbone Diagram di PT. N - Ferdiansyah, Harris; Dewi, Sinta (Fakultas Teknik Universitas Tulang Bawang, 2025)
The long travel motor on an overhead crane is a vital component that enables the crane’s horizontal movement along its track. This study aims to analyze the failure risks of the ABUS long travel motor at PT N using the Failure Mode and Effect Analysis (FMEA) and Fishbone Diagram methods. FMEA was utilized to identify critical components based on their Risk Priority Number (RPN), while the Fishbone Diagram analyzed the root causes of failure for components with the highest RPN.The results indicate that the Gear Pinion is the most critical component with an RPN value of 405, attributed to significant failure impacts, high failure frequency, and challenges in early detection. Major contributing factors include insufficient technical training, low-quality materials, inadequate lubrication, and environmental influences such as high temperatures and dust contamination. Preventive solutions include regular technical training, the use of high-quality materials, installation of automatic lubrication systems, implementation of preventive maintenance schedules, and enhanced monitoring systems. These measures are expected to reduce failures, improve operational reliability, and enhance production efficiency at PT N. Keywords : Fishbone Diagram, FMEA, Long Travel Motor.